Caveolin‐1 promotes cancer progression via inhibiting ferroptosis in head and neck squamous cell carcinoma. (19th December 2021) - Lu, Tingwei; Zhang, Zhen; Pan, Xinhua; Zhang, Jianjun; Wang, Xu; Wang, Miaochen; Li, Huasheng; Yan, Ming; Chen, Wantao
Abstract: Background: Head and neck squamous cell carcinoma (HNSCC) is an aggressive disease worldwide. Much progress has been made in exploring mechanisms and improving the therapy of HNSCC, but only a few studies have focused on the role of ferroptosis on HNSCC progression. The current study aimed to reveal the underlining mechanisms that caveolin‐1 (CAV1)‐ROS (reactive oxygen species)‐ferroptosis axis affect the process of HNSCC and discover novo therapeutic targets or strategies. Methods: The role of CAV1 in ferroptosis was analyzed by FerrDb, and its clinical significance was examined by TCGA dataset of HNSCC. The expressions of caveolin‐1 (CAV1) in HNSCC tissues were measured by immunohistochemistry, western blot, and real‐time PCR assay. Three siRNA sequences were designed to silence CAV1  mRNA in HNSCC cells. Cell proliferation, colony formation, wound‐healing, and transwell assays were used to examine the proliferation, migration, and invasion of cancer cells. ROS evaluation and intracellular Fe 2+ content assays were performed to examine the levels of ferroptosis. Results: Through the analysis with published data, CAV1 was found to overexpress in HNSCC than normal tissues, and was one of the vital suppressors of ferroptosis pathway. Our study showed that CAV1 was over expressed in HNSCC tissues and the high level of CAV1 predicted poorer prognosis. Further experiments indicated that CAV1 could inhibit the ferroptosis of cancer cells and promote the proliferation, migration and invasion. Conclusions: Overexpression of CAV1 in HNSCC inhibited the process of ferroptosis, leading to aggressive phenotypes, as well as worse prognosis. The regulatory pathway of CAV1 and ferroptosis are potential targets for designing diagnostic and combined therapeutic strategies for HNSCC patients.